2021
DOI: 10.1088/1755-1315/779/1/012117
|View full text |Cite
|
Sign up to set email alerts
|

An ecological study of the fern Asplenium Trichomanes L. in Iraq with a reference to its phytochemical and antioxidant activity

Abstract: A number of ferns are known to have ornamental, medicinal and ethnobotanical importance all over the world. In spite of the presence of numerous fern species such as Equisetum, Adiantum, Asplenium and Cheilanthes species all over our country (Iraq) particularly the Kurdistan part, still, such information in this area is quite rare. Asplenium Trichomonas L. is a genus of one of the widest groups of Asplenideae (maidenhair spleen worts). It is a megaphyllous, homosporous fern, which was found at an elevation abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Therefore, we focused our analysis on the concentrations of alkaloids to investigate the effects of these factors on the alkaloids contents of the studied ferns in Iraq. In Chemi Rezan region, the fern species survival at elevation and environment conditions varied than of Malakan region which affected the alkaloid contents in the studied fern [25,26,27]. Thee environmental factors influence the biosynthesis of alkaloids [28].…”
Section: • (------) Absentmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, we focused our analysis on the concentrations of alkaloids to investigate the effects of these factors on the alkaloids contents of the studied ferns in Iraq. In Chemi Rezan region, the fern species survival at elevation and environment conditions varied than of Malakan region which affected the alkaloid contents in the studied fern [25,26,27]. Thee environmental factors influence the biosynthesis of alkaloids [28].…”
Section: • (------) Absentmentioning
confidence: 95%
“…A previous research found that secondary metabolites accumulation is strongly dependent on environmental factors such as temperature, humidity, climate and latitude [22,23,24]. The total production of secondary metabolites in plants may form maximally related to the environment, biotic, abiotic stresses and nutrient [25], light [26], climate [27], altitude [6] and latitude [22]. Therefore, we focused our analysis on the concentrations of alkaloids to investigate the effects of these factors on the alkaloids contents of the studied ferns in Iraq.…”
Section: • (------) Absentmentioning
confidence: 99%